Chalcones: A review on synthesis and pharmacological activities - Kamya Goyal&, Rajwinder Kaur, Anju Goyal, Rajendra Awasthi (Journal of Applied Pharmaceutical Science, 2021)
Chalcone is a privileged species with medicinal significance as it consists of reactive ketoethylenic moiety –CO– CH=CH– belonging to flavonoids. The presence of a reactive α, β-unsaturated carbonyl function in chalcone and its derivatives is the reason for its pharmacological activities. Chalcones exhibit a wide spectrum of pharmacological effects such as antioxidant, antibacterial, anthelmintic, antiulcer, antiviral, insecticidal, antiprotozoal, anticancer, antiinflammatory, antidiabetic, etc. Chalcones can be synthesized by Claisen–Schmidt’s condensation, Heck’s reaction, Suzuki’s reaction, etc. The purpose of this review is to focus on the methods of synthesis of chalcones and their versatile pharmacological activities.
Keywords: Chalcone, Claisen–Schmidt condensation, anticancer, antimicrobial, antidiabetic.